Viral eaudiobook - Cook, Robin (Pia Grazdani., 2021)
In this electrifying medical thriller from New York Times bestselling author Robin Cook, a family’s exposure to a rare yet deadly virus ensnares them in a growing danger to mankind—and pulls back the curtain on a healthcare system powered by profit and greed. Trying to find some normalcy during the Covid-19 pandemic, Brian Murphy and his family are on a summer excursion in Cape Cod when his wife, Emma, comes down with concerning flu-like symptoms. But their leisurely return home to New York City quickly becomes a race to the local hospital as she suddenly begins seizing in the car. At the ICU, she is diagnosed with eastern equine encephalitis, a rare and highly lethal mosquito-borne viral disease seemingly caught during one of their evening cookouts. Complicating the situation further, Brian and Emma’s young daughter then begins to exhibit alarming physical and behavioral symptoms, too.   Emma’s harrowing hospital stay becomes even more fraught when Brian receives a staggering hospital bill full of outrageous charges and murky language. To add insult to injury, his health insurance company refuses to cover any of the cost, citing dubious clauses in Brian’s policy. Forced to choose between the ongoing care of family and bills he can never pay, and furious at a shockingly indifferent healthcare system, Brian vows to seek justice. But to get to the bottom of the predatory practices targeting his loved ones and countless others, he must uncover the dark side of an industry that has strayed drastically from its altruistic roots—and bring down the callous executives preying on the sick and defenseless before the virus can claim even more people . . .